Development Of Wireless Power Transfer Using Capacitive Method For Mouse Charging Application - Mohd Shakir, Md Saat; Ong, Zhen Guat; Farah Khalidah, Abdul Rahman; Azmi, Awang Md Isa; Abdul Majid, Darsono (Institute Of Advanced Engineering And Science (IAES), 2016)
Wireless power transfer (WPT) is a non-contact power transfer within a distance. With the advantage of not-contact concept, WPT enhances the flexibility movement of the devices. Basically, there are three types of the WPT which are inductive power transfer (IPT), capacitive power transfer (CPT) and acoustic power transfer (APT). Among these, capacitive power transfer (CPT) has the advantages of confining electric field between coupled plates, metal penetration ability and also the simplicity in circuit topologies. Therefore, we focus on the capacitive method in this paper. To be specific, this paper aims to develop a wireless mouse charging system using capacitive based method. This method enables wireless power transmission from mouse pad to a wireless mouse. Hence, no battery requires to power up the mouse. In this paper, a high efficiency Class-E converter is described in details to convert the DC source to AC and the compensation circuit of resonant tank is also proposed at the transmitter side in order to improve the efficiency. In the end, a prototype is developed to prove the developed method. The performances analysis of the developed prototype is discussed and the future recommendation of this technique is also presented.